2 VENOUS IRRITATION WITH CORDARONE IV AND TWO DIFFERENT FORMULATIONS OF AQUEOUS AMIODARONE WHEN ADMINISTERED VIA PERIPHERAL VEINS. (1st March 2005) - Somberg, J. C.; Ranade, V.; Cvetanovic, I.; Molnar, J.
Abstract : Background: Intravenous amiodarone is irritable to the venous system and should be administered through a central venous catheter whenever possible. However, amiodarone is often administered via a peripheral vein. The controlled trials for Cordarone IV primarily employed central venous lines and did not provide sufficient information about the risk of peripheral drug administration. This study evaluated the venous irritation with Cordarone IV (Wyeth) and 2 aqueous formulations of intravenous amiodarone: Amio-Aqueous, the original aqueous formulation (Academic Pharmaceuticals), and Amiodarone Aqueous IV, produced by a different manufacturing process (Wyeth). Each intravenous formulation suspends amiodarone as a micelle. Methods: In a series of controlled trials, patients were randomized to either Amio-Aqueous or lidocaine, or to either Cordarone IV or Amiodarone Aqueous IV. Therapy with Amio-Aqueous and Amiodarone Aqueous IV were initiated with boluses of 150 mg amiodarone (10 mL, 15 mg/mL), Cordarone IV was initiated with 10-minute infusion (75 mL, 2 mg/mL), all were followed with a 24-hour infusion delivering 900-1150 mg amiodarone over 24 hours. Therapy with lidocaine was initiated with 100 mg boluses followed by a 24-hour infusion. Results: A total of 177 patients received Cordarone IV, 168 patients received Amiodarone Aqueous IV, 185 received Amio-Aqueous, and 127 received lidocaine. The most common adverse events for Amiodarone Aqueous IV and Cordarone IV were injection site inflammation (60% and 32%), injection site pain (55% and 22%), injection site edema (50% and 17%), and phlebitis (35% and 6%), p<0.001. In contrast, the incidence of venous irritation was 2% for Amio-Aqueous with phlebitis in 1.6% (p<0.001). There was no venous irritation with lidocaine. X-ray diffraction studies showed that the physical nature of the two aqueous formulations (Amiodarone Aqueous IV and Amio-Aqueous) were different. Conclusions: Both Cordarone IV and Amiodarone Aqueous IV are irritative to the venous system, while Amio-Aqueous is not, a difference that could relate to the different micelle structure of amiodarone among the formulations. The original aqueous formulation (Amio-Aqueous) appears to lack significant venous irritation and may be administered via a peripheral vein.